THE LOW-BORON CONTEST: MINIMISING SURFACE CONTAMINATION AND ANALYSING BORON CONCENTRATIONS AT THE NG/G-LEVEL BY SECONDARY ION MASS SPECTROMETRY - Marschall H.R.; Ludwig T. (My University, 2004)
In-situ analyses of boron using secondary ion mass spectrometry (SIMS) is impeded by surface contamination of the analysed samples. We analysed 40 different natural and synthetic silicate materials, including meteoritic and mantle minerals, in order to find a material with an extremely low boron content that allows us to quantify the level of contamination. Different cleaning procedures were tested, and it was shown that using an ultrasonic cleaner with ultrapure water to clean the sample and setting the imaged field of the ion probe smaller than the primary beam spot reduces the boron contamination level to <2 ng/g at a total analysis time of ∼12 min (pre-sputtering: 400 s). Herasil 102, a pure synthetic SiO2 glass manufactured by Heraeus Quarzglas GmbH, Germany, was found to contain ≤1 ng/g boron, and therefore we recommend this glass as a sample to test the contamination level of boron in SIMS analyses. Results for lithium show that analysis of this element is also influenced by contamination, but the contamination levels are much lower than those for boron.